An Approach to the Teaching of English in Indonesia - WILLEM SARAGIH (BAHAS, 2012)
Due to its great role which is now globalizing, to be able to communicate in English well is a dream of all people over the world, including Indonesians. However, it is not easy for non-English people to learn the language, especially for those whose native language is so greatly different in terms of the pronunciation, spelling, and grammatical features. For Indonesian people, generally, English is not easy to learn that efforts to facilitate he learners’ English language acquisition have been made from time to time for example by changing or evaluating the English Curriculum, the teaching methods, etc. Until now, there has not been a single method or technique known to be truly effective and efficient to use in teaching the language to the Indonesian students. This article presents some views which need considering for the success of the learning of English in Indonesia. That intrinsic learning motivation which results from self-awareness of the English language great role in everyone’s study or career is advisable to be possessed by the learners is one main factor for their good success in learning the language. Therefore, it should be socialized to the children as early as possible. In learning the English words, the teacher should familiarize the students with how every word is used in context, not in isolation as words actually do not carry clear meanings in isolation. The meaning of a word is determined by its context, so it should be contextually studied. The aspects of grammar to he dealt with also should be based on the dominant grammatical mistakes in the sentences made by the learners so as to arouse their curiosity and interest in acquiring the language. The outdated thinking that one who is using English at public places is regarded as showing off or conceited, and the language should be used only in the classroom or at certain occasions, should be eradicated now since it hampers language acquisition.